Special Needs English Teacher’s Strategies for ADHD Student in Vocabulary Mastery Focus (Scripta : English Department Journal, 2026)
Vocabulary mastery is important in English learning, especially for students with Attention Deficit Hyperactivity Disorder (ADHD), who often struggle to maintain attention, remember new words, and participate actively in class. This study explored how a shadow teacher supported English vocabulary learning for a student with ADHD in an inclusive senior high school classroom in North Sumatera, Indonesia. A qualitative case study design was used, with data gathered through interviews with the shadow teacher and English teacher, classroom observations, and document analysis of lesson plans and vocabulary records. The shadow teacher served as primary informant, given three years of daily engagement with the student. Thematic analysis revealed two areas: (1) strategies supporting vocabulary learning, including individualized assistance, repeated practice, emotional guidance, reinforcement, and audio-visual media; and (2) challenges including sustaining attention, limited collaboration, and absent ADHD training. Document analysis corroborated these findings, showing strong vocabulary performance alongside lesson plans with no curricular adaptation. The shadow teacher's role extended beyond academic assistance to include emotional and motivational support, with effectiveness depending on combined strategies rather than a single approach. These findings highlight the need for stronger collaboration, flexible support, and professional development to help shadow teachers work effectively with ADHD students.